Comparison of NASAL colonization of MRSA in people living with HIV and healthy community people. - Kapali,Samjhana (2020)
ABSTRACT: People living with human immunodeficiency virus (PLHIV) are frequently exposed to antimicrobial agents that may have an impact on the resistance pattern of Staphylococcus aureus leading to the complication in therapeutic treatments. PLHIV have reduced immunity that are recognized as the higher risk groups due to increased rates of methicillin-resistant Staphylococcus aureus (MRSA) colonization and infections over the past decades. So, this study aims to compare the nasal colonization of MRSA in PLHIV and healthy community people. A total of 400 nasal swabs were collected from anterior nares of 200 PLHIV at tertiary care hospital and 200 community people in Kathmandu. Staphylococcus aureus isolates were identified by conventional microbiological methods and subjected to antimicrobial susceptibility test using Kirby Bauer disc diffusion method. MRSA was screened using cefoxitin disk, and confirmed by PCR detection of the mecA gene. Panton Valentine Leukocidin (PVL) gene among S. aureus isolates was detected as a marker for community acquired isolates. From the total 400 nasal swabs, 42 (10.5%) S. aureus were isolated out of which 17 (42.5%) were MRSA strains. Among the S. aureus isolates, by detecting the mecA gene, 7 (41.2%) and 10 (40%) MRSA were confirmed in PLHIV and healthy controls, respectively. All the MRSA isolates 7 (100%) from PLHIV and only 8 (80%) of MRSA from healthy controls were PVL positive strains. The prevalence rates of MDR S. aureus among PLHIV and healthy controls were 11(64.7%) and 16(64%) in healthy controls respectively with the total MDR S. aureus rate as 27 (64.3%) in the study. For the both groups, the MRSA colonization was statistically significant in subjects with a history of hospitalization in the past 6 months (pvalue <0.05) however, age was not associated with MRSA and S. aureus colonization. The lower odds of nasal colonization by S. aureus and MRSA were associated with the longer antiretroviral therapy (ART) duration in PLHIV with p-value of 0.039 and 0.014 respectively. In PLHIV with CD4 count <200 cells/µl, MRSA colonization (22.2% versus 5%) and S. aureus (27.8% versus 12.5%) colonization were around 4 folds higher and around 2 folds higher than in healthy controls respectively. The study shows that wellmonitored ART may have reduced the risk of S. aureus and MRSA nasal colonization but CD4 count <200 cells/µl, may be related with the nasal colonization by the bacteria in PLHIV. Also, PLHIV are more susceptible to community acquired MRSA. However, genotyping of PVL subtypes would provide a more accurate way of tracking the dissemination of S. aureus. Well monitored ART would indirectly help to reduce MRSA nasal colonization. The factors like recent use of antibiotics and history of cotrimoxazole prophylaxis should be studied to conclude higher MRSA colonization among PLHIV. Keywords: PLHIV, Staphylococcus aureus, MRSA, mecA, PVL